Comparison of the Legal Regulation of the Rechterlijk Pardon in Indonesia and the Netherlands - Estiningtyas, Aulia Rizka; Ulfatul Hasanah; Windari, Rusmilawati (Jurnal Suara Hukum, 2024)
The concept of rechterlijk pardon represents a new legal formulation introduced in Indonesia through Law Number 1 of 2023 concerning the Criminal Code, aimed at aligning criminal law with contemporary societal conditions. Beyond traditional deterrence, this concept empowers judges to consider mitigating circumstances and individual offender situations. Several European countries, including the Netherlands, have long regulated rechterlijk pardon, prompting a comparative analysis of its application between the Netherlands and Indonesia. This normative legal research compares the provisions of rechterlijk pardon in the Indonesian Criminal Code (KUHP) with those in Dutch law. The findings reveal both similarities and differences: both systems require judges to justify their decision for granting pardon and offer alternative pardon requirements, yet Indonesia includes specific considerations of justice not detailed in Dutch law. The study underscores the importance of clarifying the criteria for rechterlijk pardon implementation in Indonesia to preempt potential conflicts. Ultimately, the research advocates for a clear and harmonized framework for judicial pardon in Indonesia, ensuring consistency and fairness in its application within the criminal justice system